Combination Therapy of the Active KRAS-Targeting Antibody inRas37 and a PI3K Inhibitor in Pancreatic Cancer - Lee, Ji Eun; Woo, Min Gyu; Jung, Kyung Hee; Kang, Yeo Wool; Shin, Seung Min; Son, Mi Kwon; Fang, Zhenghuan; Yan, Hong Hua; Park, Jung Hee; Yoon, Young Chan; Kim, Yong Sung; Hong, Soon Sun (Biomolecules and Therapeutics, 2022)
KRAS activating mutations, which are present in more than 90% of pancreatic cancers, drive tumor dependency on the RAS/ mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K)/AKT signaling pathways. Therefore, combined targeting of RAS/MAPK and PI3K/AKT signaling pathways may be required for optimal therapeutic effect in pancreatic cancer. However, the therapeutic efficacy of combined MAPK and PI3K/AKT signaling target inhibitors is unsatisfactory in pancreatic cancer treatment, because it is often accompanied by MAPK pathway reactivation by PI3K/AKT inhibitor. Therefore, we developed an inRas37 antibody, which directly targets the intra-cellularly activated GTP-bound form of oncogenic RAS mutation and investigated its synergistic effect in the presence of the PI3K inhibitor BEZ-235 in pancreatic cancer. In this study, inRas37 remarkably increased the drug response of BEZ-235 to pancreatic cancer cells by inhibiting MAPK reactivation. Moreover, the co-treatment synergistically inhibited cell proliferation, migration, and invasion and exhibited synergistic anticancer activity by inhibiting the MAPK and PI3K pathways. The combined administration of inRas37and BEZ-235 significantly inhibited tumor growth in mouse models. Our results demonstrated that inRas37 synergistically increased the antitumor activity of BEZ-235 by inhibiting MAPK reactivation, suggesting that inRas37 and BEZ-235 co-treatment could be a potential treatment approach for pancreatic cancer patients with KRAS mutations.
Keywords: BEZ-235; KRAS; Pancreatic cancer; PI3K; Targeting antibody